Psychological evaluation of adult burn survivors: a pilot study - Kurian, Silvana; Padickaparambil, Sebastian; Thomas, Joseph; Sreekumar, N. C.; James, Alphy Rose (International Surgery Journal, 2019)
Background: Survivors of disfiguring burn injury often become social handicaps. Therefore, it is of utmost importance to understand their perception of body image, their coping skills, their appraisals about social support and self-monitoring behaviour in social situations and explore the factors that can promote better psychological adjustment. Methods: Using a single group cohort design, a sample of 18 individuals with burn injury, were recruited through purposive sampling. Personal data sheet, self-monitoring scale (SMS) and satisfaction with appearance scale (SWAP) were administered when the patients were admitted post-injury. Social support appraisal scale (SSA), coping with burns questionnaire along with SMS and SWAP were administered at one-month post-discharge. Results: The findings indicated that gender and education played a significant role in body image, coping, social support appraisal and self-monitoring behaviours. Further, higher scores on coping strategies were associated with better body satisfaction. Conclusions: The findings indicate the need to look into the variables of coping, body image, social support, self-monitoring behaviours of burns patients and the need to develop interventions for improving their quality of life. A mixed-method study design for better understanding of the psychosocial factors impacting adjustment post-burn injury would be beneficial. Although a larger cohort needs to be studied for understanding the impact of these factors, one may already notice definite indicators that are risk factors that may lead to poorer psycho-social wellbeing of burn victims and potential areas where interventions may be effective.